An assessment of impact of information and communication technology in enterprızes of Korça region - Rafail Prodani; Jozef Bushati; Aigars Andersons (Insights into Regional Development)
Ever-evolving and increasingly powerful Information and Communication Technologies (ICTs) have fundamentally changed the nature of global relationships, sources of competitive advantage and opportunities for economic and social development. ICTs have greatly increased the impact on every area of human life. Technologies such as the Internet, personal computers and wireless have turned the globe into a network of individuals, businesses, governments, and ever-growing schools who communicate and interact with one another. Without doubt ICTs plays a strategic role in managing organizations. This paper presents a part of the current state of ICTs for enterprises by establishing comparative bases for further studies in this field. It also helps academic institutions to evaluate and identify factors, as well as the specific role and weight of these factors have in the process of developing ICTs towards a developed economy and society in the context of digital Albania. It is presented as a scientific analyse, accomplished, detailed and expressed in percentage and graphical analysis of a number of very important data sets of enterprises in their full form, to unlock developments in the field of ICTs in our country, including specific ones based on concrete data. This study tends to study the extent to which these but have involved ICTs and what impact these technologies have in the daily work of these organizations in part of Albania (Korca Region)and brings its contribution as a perspective of literature, experience and international studies, the level of development of our country regarding the assessment of electronic readiness of business organizations.